Oral toxicity of titanium dioxide P25 at repeated dose 28-day and 90-day in rats - Min Beom Heo (Particle and Fibre Toxicology, 2020)
Abstract Background Nanotechnology is indispensable to many different applications. Although nanoparticles have been widely used in, for example, cosmetics, sunscreen, food packaging, and medications, they may pose human safety risks associated with nanotoxicity. Thus, toxicity testing of nanoparticles is essential to assess the relative health risks associated with consumer exposure. Methods In this study, we identified the NOAEL (no observed adverse effect level) of the agglomerated/aggregated TiO2 P25 (approximately 180 nm) administered at repeated doses to Sprague-Dawley (SD) rats for 28 and 90 days. Ten of the 15 animals were necropsied for toxicity evaluation after the repeated-dose 90-day study, and the remaining five animals were allowed to recover for 28 days. The agglomerated/aggregated TiO2 P25 dose levels used included 250 mg kg− 1 d− 1 (low), 500 mg kg− 1 d− 1 (medium), and 1000 mg kg− 1 d− 1 (high), and their effects were compared with those of the vehicle control. During the treatment period, the animals were observed for mortality, clinical signs (detailed daily and weekly clinical observations), functional observation battery, weekly body weight, and food and water consumption and were also subjected to ophthalmological examination and urinalysis. After termination of the repeated-dose 28-day, 90-day, and recovery studies, clinical pathology (hematology, blood coagulation time, and serum biochemistry), necropsy (organ weights and gross findings), and histopathological examinations were performed. Results No systemic toxicological effects were associated with the agglomerated/aggregated TiO2 P25 during the repeated-dose 28-day, 90-day, and recovery studies in SD rats. Therefore, the NOAEL of the agglomerated/aggregated TiO2 P25 was identified as 1000 mg kg− 1 d− 1, and the substance was not detected in the target organs. Conclusion Subacute and subchronic oral administration of the agglomerated/aggregated TiO2 P25 was unlikely to cause side effects or toxic reactions in rats.